Dancing with the river : people and life on the chars of South Asia - Lahiri-Dutt, Kuntala, 1956- (Yale agrarian studies., 2013)
This book offers an intimate glimpse into the microcosmic world of 'hybrid environments.' Focusing on chars--the part-land, part-water, low-lying sandy masses that exist within the riverbeds in the floodplains of lower Bengal--the authors show how, both as real-life examples and as metaphors, chars straddle the conventional categories of land and water, and how people who live on them fluctuate between legitimacy and illegitimacy. The result, a study of human habitation in the nebulous space between land and water, charts a new way of thinking about land, people, and people's ways of life.